Integrated Analysis of MicroRNA and Target Genes in Brachypodium distachyon Infected by Magnaporthe oryzae by Small RNA and Degradome Sequencing - Peng, Weiye; Song, Na; Li, Wei; Yan, Mingxiong; Huang, Chenting; Yang, Yang; Duan, Kangle; Dai, Liangying; Wang, Bing (Frontiers in Plant Science, 2021)
Rice blast caused by Magnaporthe oryzae is one of the most important diseases that seriously threaten rice production. Brachypodium distachyon is a grass species closely related to grain crops, such as rice, barley, and wheat, and has become a new model plant of Gramineae. In this study, 15 small RNA libraries were built to examine the dynamic changes in miRNA expression in B. distachyon infected by M. oryzae at 0, 24, and 48 h after inoculation. We identified 432 conserved miRNAs and 288 predicted candidate miRNAs in B. distachyon. Additionally, there were 7 and 19 differentially expressed miRNAs at 24 and 48 h post-inoculation, respectively. Furthermore, using degradome sequencing, we identified 2126 genes as targets for 308 miRNAs; using qRT-PCR, we validated 5 miRNA/target regulatory units during B. distachyon–M. oryzae interactions. Overall, using co-transformation technology, our study demonstrated that BdNAC21 is negatively regulated by miR164c, thus providing a new approach for identifying B. distachyon resistance genes by mining the miRNA regulatory network of host–pathogen interactions.